Exploring Students’ Independent Learning and Teachers’ Support in EFL Classrooms: A Constructivist Approach - Nailah; Neni Afrida Sari Harahap; Karunia Devi Frida (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2025)
This study aims to identify student's perception about independent learning and activities and also how their teachers encourage independent learning during English class. The research used qualitative method to obtain student's perception. The source of data is 20 students from SMA Brigjend Katamso 1 Medan which Student's perception and experience are the data. Open and close ended questionnaire are used as instruments to collect the data. The close-ended responses are analyzed using simple descriptive statistics (such as percentages), whereas the open-ended responses are categorized into themes to capture the underlying meanings and insights. The results indicate that while students actively engage in independent learning activities, teacher support and encouragement for such independent learning in the classroom is still limited